A remarkable new species of Trissolcus Ashmead (Hymenoptera, Scelionidae), parasitoid of eggs of Phloea subquadrata (Hemiptera, Phloeidae) in Brazil - Valmir A. Costa; Norman Johnson; Adriana Salomão; João Vasconcellos-Neto; Ana Wengrat; Karine Schoeninger (Journal of Hymenoptera Research)
Trissolcus adrianae Costa & Johnson, sp. nov. is described. It is an egg parasitoid of the neotropical bark bug Phloea subquadrata Spinola (Hemiptera, Phloeidae) on Plinia cauliflora (Mart.) Kausel (Myrtales, Myrtaceae). Trissolcus adrianae belongs to the flavipes species group and can easily be distinguished from other flavipes group members by its noticeably depressed habitus; head oblong in anterior view; bidentate mandibles; frontal depression delimited dorsally by carina; orbital furrow sculptured, constricted through most of its length by lateral expansion of frons; notauli absent; and the length of T3–T6 subequal to the length of T2. This is the first species of Scelionidae associated with the family Phloeidae (Hemiptera: Pentatomoidea) and the first report of parasitism of Phloeidae eggs as well.